PENGARUH GERAK MAKAN DAN KECEPATAN POTONG TERHADAP KEKASARAN PERMUKAAN BAJA HQ 705 PADA PROSES PEMBUBUTAN - Ismet Eka Putra; Agus Wendi Syaputra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2015)
Quality products are obtained from the good machining process. Surface roughness is either aberrations caused by the cutting conditions of the machining process. HQ 705 is a mixture of hardened steel machining with high quality used in gear, shaft engines, and other machined components. It so conducted experiments to analyze the effect of feeding and cutting speed of motion of the surface roughness of the steel HQ 705 at the turning process. To determine the surface roughness at experiments using surface roughness tester. Experiments conducted at varying cutting speed are 40 m / min, 60 m / min, and 80 m / min. The cutting speed is set at spindle rotation 740 RPM, 900 RPM and 1230 RPM. Turning at motion feeding variated 0.05 mm / r and 0.22 mm / r. Depth of feeding made of 1 mm for any specimen. The experiment is obtained at surface roughness of motion feeding 0.05 mm / r obtained roughness value of 1.43 μm with a cutting speed of 77.28 m / min, at motion feeding 0.22 mm / r obtained roughness values of 4.296 μm with cutting speed of 46.50 m / min. HQ 705 with a conventional turning obtained roughness value is normal, at motion feeding 0.05 mm/r and depth of cut of 1 mm.